2021
DOI: 10.1002/mco2.101
|View full text |Cite
|
Sign up to set email alerts
|

Nasally inhaled therapeutics and vaccination for COVID‐19: Developments and challenges

Abstract: The nose is the initial site of viral infection, replication, and transmission in the human body. Nasally inhaled vaccines may act as a promising alternative for COVID‐19 management in addition to intramuscular vaccination. In this review, the latest developments of nasal sprays either as repurposed or antiviral formulations were presented. Nasal vaccines based on traditional medicines, such as grapefruit seed extract, algae‐isolated carrageenan, and Yogurt‐fermenting Lactobacillus , are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 116 publications
0
21
0
Order By: Relevance
“…Nevertheless, the major challenges in the development of nasal vaccines are the delivery of antigen to APC in the respiratory tract and the safety issue. Approaches to overcome these obstacles include the use of a safe and effective adjuvant and delivery system to increase the efficacy and prolong the time of antigen uptake in the respiratory tract [255][256][257][258]. In this regard, TLR agonist-based nasal adjuvants are continuously being developed.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the major challenges in the development of nasal vaccines are the delivery of antigen to APC in the respiratory tract and the safety issue. Approaches to overcome these obstacles include the use of a safe and effective adjuvant and delivery system to increase the efficacy and prolong the time of antigen uptake in the respiratory tract [255][256][257][258]. In this regard, TLR agonist-based nasal adjuvants are continuously being developed.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the intranasal administration of the HIV-1 vaccine induced strong mucosal immune responses against HIV mucosal infections [ 8 , 9 , 10 , 11 , 12 ]. Additionally, inoculation via aerosol sprays or droplets is an attractive way to deliver COVID-19 vaccines [ 71 , 72 ].…”
Section: Challenges and Solutions For The Development Of Mucosa-targe...mentioning
confidence: 99%
“…Clinical trials of inhaled vaccines and therapeutics in the form of nasal sprays have been conducted using existing or modified vaccines, such as Carrageenan, Povidone‐Iodine, Ivermectin, Xylitol, etc 5 . The recent study by Afkhami et al.…”
Section: Figurementioning
confidence: 99%
“…4 Clinical trials of inhaled vaccines and therapeutics in the form of nasal sprays have been conducted using existing or modified vaccines, such as Carrageenan, Povidone-Iodine, Ivermectin, Xylitol, etc. 5 The recent study by Afkhami et al demonstrated that mucosal immunization using Adenoviral-vectored multivalent vaccines could be a convenient, cost-efficient, and painless vaccination strategy to achieve adequate protection against COVID-19 infections. 1 Even a single-dose intranasal application induced allaround mucosal immunity against ancestral SARS-CoV-2 and variant strains.…”
mentioning
confidence: 99%